What about tocilizumab? A retrospective study from a NYC Hospital during the COVID-19 outbreak. - Monica Mehta; Lawrence J Purpura; Thomas H McConville; Matthew J Neidell; Michaela R Anderson; Elana J Bernstein; Donald E Dietz; Justin Laracy; Shauna H Gunaratne; Emily Happy Miller; Jennifer Cheng; Jason Zucker; et al. (PLoS ONE, 2021)
Background Tocilizumab, an interleukin-6 receptor blocker, has been used in the inflammatory phase of COVID-19, but its impact independent of corticosteroids remains unclear in patients with severe disease. Methods In this retrospective analysis of patients with COVID-19 admitted between March 2 and April 14, 2020 to a large academic medical center in New York City, we describe outcomes associated with tocilizumab 400 mg (without methylprednisolone) compared to a propensity-matched control. The primary endpoints were change in a 7-point ordinal scale of oxygenation and ventilator free survival, both at days 14 and 28. Secondary endpoints include incidence of bacterial superinfections and gastrointestinal perforation. Primary outcomes were evaluated using t-test. Results We identified 33 patients who received tocilizumab and matched 74 controls based on demographics and health measures upon admission. After adjusting for illness severity and baseline ordinal scale, we failed to find evidence of an improvement in hypoxemia based on an ordinal scale at hospital day 14 in the tocilizumab group (OR 2.2; 95% CI, 0.7-6.5; p = 0.157) or day 28 (OR 1.1; 95% CI, 0.4-3.6; p = 0.82). There also was no evidence of an improvement in ventilator-free survival at day 14 (OR 0.8; 95% CI, 0.18-3.5; p = 0.75) or day 28 (OR 1.1; 95% CI, 0.1-1.8; p = 0.23). There was no increase in secondary bacterial infection rates in the tocilizumab group compared to controls (OR 0.37; 95% CI, 0.09-1.53; p = 0.168). Conclusions There was no evidence to support an improvement in hypoxemia or ventilator-free survival with use of tocilizumab 400 mg in the absence of corticosteroids. No increase in secondary bacterial infections was observed in the group receiving tocilizumab.